2017
DOI: 10.1111/petr.13089
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared spectroscopy might be a useful tool for predicting the risk of vascular complications after pediatric liver transplants: Two case reports

Abstract: In patients that have undergone liver transplants, a postoperative reduction in the blood flow of the liver graft represents a critical complication. We recently encountered an interesting phenomenon; that is, we found that the rSO level of the liver graft, as measured by NIRS, drops in patients that subsequently require an emergency liver biopsy. An 8-month-old female and an 8-month-old male underwent living donor liver transplants for biliary atresia. In both cases, a reduction in rSO was detected before an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
1
7
1
Order By: Relevance
“…At the moment, NIRS contributed to the early diagnosis of vascular complications in two children who undergone liver transplantation. 16 However, even if kidney rSrO2 was not altered amongst the patients affected by DGF in the series by Vidal et al, the authors suggested that NIRS might help in discriminating the causes of oligo-anuria in the early post-operative time after KT, helping in managing the postoperative fluid balance. 8 Recently, an experimental study successfully tested a NIRS wireless device implanted on the surface of the kidney.…”
Section: Discussionmentioning
confidence: 95%
“…At the moment, NIRS contributed to the early diagnosis of vascular complications in two children who undergone liver transplantation. 16 However, even if kidney rSrO2 was not altered amongst the patients affected by DGF in the series by Vidal et al, the authors suggested that NIRS might help in discriminating the causes of oligo-anuria in the early post-operative time after KT, helping in managing the postoperative fluid balance. 8 Recently, an experimental study successfully tested a NIRS wireless device implanted on the surface of the kidney.…”
Section: Discussionmentioning
confidence: 95%
“…However, Shiba et al described NIRS monitoring in two children encountering vascular complications after liver transplantation. In these cases, decreasing rSO2 values might suggest the occurrence of vascular adverse events 5 …”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative tissue oxygenation status may be a composite marker of the balance between oxygen supply and consumption, which is largely determined by hemodynamic perfusion, a venous-weighted mixture of venous and arterial hemoglobin-oxygen saturation, and anesthetic-suppressed or surgical stress-related elevation of the metabolic rate [30]. SstO 2 is an emerging marker of early postoperative complications in patients undergoing LT; however, SstO 2 measurement sites differ among LT studies [9][10][11]. In an intensive care unit study by Civantos et al, the oximetry sensor was placed on the dermatome overlying the liver allograft [9].…”
Section: Plos Onementioning
confidence: 99%
“…SstO 2 was significantly associated with the cardiac index, hemoglobin, and APACHE II score. Shiba et al reported that a reduction in SstO 2 (monitored on the dermatome overlying the liver allograft) was associated with an increased risk of acute graft rejection [10]. Hu et al reported that full drainage of ascites during LT led to an increased leg SstO 2 ; however, IVC clamping and abdominal hypertension caused a significant reduction in the leg SstO 2 .…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation